2018
DOI: 10.3390/ijerph15112329
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and Acceptability of Infectious Disease Interventions Among Migrants in the EU/EEA: A CERQual Systematic Review

Abstract: In the EU/EEA, subgroups of international migrants have an increased prevalence of certain infectious diseases. The objective of this study was to examine migrants’ acceptability, value placed on outcomes, and accessibility of infectious disease interventions. We conducted a systematic review of qualitative reviews adhering to the PRISMA reporting guidelines. We searched MEDLINE, EMBASE, CINAHL, DARE, and CDSR, and assessed review quality using AMSTAR. We conducted a framework analysis based on the Health Beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
(96 reference statements)
1
10
0
Order By: Relevance
“…This systematic review identified barriers and facilitating factors for HBV and HCV screening in migrants in the EU/EEA region. Many of the here identified factors were in line with previous review-studies examining infectious disease screening initiatives among migrants ( 13 , 16 , 92 , 93 ). By discussing concepts according to seven domains inspired by Flottorp, Oxman ( 19 ), Grol and Wensing ( 20 ), and Fleuren, Paulussen ( 21 ), we allowed the inclusion of less frequently featured domains, such as healthcare innovations, since in recent years more innovations are being applied in screening, such as rapid POCT ( 84 , 86 , 88 ).…”
Section: Discussionsupporting
confidence: 85%
“…This systematic review identified barriers and facilitating factors for HBV and HCV screening in migrants in the EU/EEA region. Many of the here identified factors were in line with previous review-studies examining infectious disease screening initiatives among migrants ( 13 , 16 , 92 , 93 ). By discussing concepts according to seven domains inspired by Flottorp, Oxman ( 19 ), Grol and Wensing ( 20 ), and Fleuren, Paulussen ( 21 ), we allowed the inclusion of less frequently featured domains, such as healthcare innovations, since in recent years more innovations are being applied in screening, such as rapid POCT ( 84 , 86 , 88 ).…”
Section: Discussionsupporting
confidence: 85%
“…Social determinants of health and health systems play a critical factor in determining refugee and migrant patient access to primary health care [ 16 ]. Indeed, prior to COVID-19, refugee access to care was limited due to income, unemployment, literacy, housing, social exclusion, race and official language skills [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These reviews discuss the effectiveness and cost effectiveness of screening for HIV, hepatitis B and C, schistosomiasis, and strongyloidiasis. The articles also discuss the effectiveness of interventions (including vaccinations) and their cost effectiveness in migrants in the EU/EEA (Table 1) [9,10,11,12,15,16]. These have led to a recent publication of the European Center for Disease Prevention and Control (ECDC) entitled “Public health guidance on screening and vaccination for infectious diseases in newly arrived migrants within the EU/European Economic Area (EEA)” [46].…”
Section: Review Of Articles In the Special Issuementioning
confidence: 99%
“…Factors associated with accessibility and acceptability of interventions to prevent infectious disease included knowledge of the disease and the related stigma, as well as migrants’ interaction with HC providers [16].…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation